Categorization behavior of medical doctors and non-medical professionals a case study - Quiros, Edgardo B. (2001)
Commercial scale production of indexes particularly for medical databases had challenged traditional practices in information processing. The need to recruit and train indexers efficiently for a commercial scale indexing has stimulated the conduct of this research. This research dealt on how medical and non-medical professionals assign artificial categories to medical and non-medical documents using multiple-case replication methodology. Specifically, the study focused on how a professional indexer with a medical degree and five professional indexers without a medical degree assigned forty-four categories to medical and non-medical journal articles; and on how medical and non-medical professionals without indexing experience assigned forty-four artificial categories to medical and non-medical journal articles.